Platelet count: A predictor of sepsis and mortality in severe burns. Issue 2 (March 2018) - Cato, Liam D.; Wearn, Christopher M.; Bishop, Jonathan R.B.; Stone, Matthew J.; Harrison, Paul; Moiemen, Naiem
Highlights: Platelet count follows a nadir at days 2–4 and peaks between days 13 and 14. Time courses for platelet counts are different when split by mortality and sepsis. Platelet count and rBaux score may aid discrimination of survival within 24 h. There is some association between the nadir platelet count and sepsis. Abstract: Background: Platelet cells, or thrombocytes, have additional roles to haemostasis. After burn injury, platelet counts drop to a nadir at days 2–5 then rise to a peak between days 10–18. The nadir has previously been associated with mortality but there is currently no thorough investigation of its potential to predict sepsis in adults. The primary objective of this study is to assess whether platelet count can predict survival and sepsis in adults with severe burn injuries. Methods and findings: A retrospective cohort analysis of platelet count and other blood parameters in 145 burn patients with a TBSA greater than 20%. AUROC analysis revealed that the platelet count and rBaux score together produce moderate discrimination for survival at less than 24 h after injury (AUROC = 0.848, 95%CI 0.765–0.930). Platelet count at day 3 combined with TBSA has a modest association with sepsis (AUROC = 0.779, 95%CI 0.697–0.862). Multivariable Cox regression analysis revealed platelet peak was the strongest predictor of mortality. Conclusions: A reduced peak platelet count is a strong predictor of 50-day mortality. Platelet count nadir may have some association with sepsis.